Effect of deposit chemistry on the stress corrosion cracking susceptibility of CMSX-10 at 550°C and 700°C - Martinez, Fabian Duarte; Syed, Adnan U.; Gibson, Grant J.; Leggett, Jonathan; Mason-Flucke, Julian C.; Nicholls, John R.; Gray, Simon (Springer, 2026)
Turbine blades of aerogas turbines can be at risk of stress corrosion cracking (SCC) below 700 °C due to the effects of stress, sulphur-containing gases and deposits that are ingested into the turbine. Therefore, understanding the effect of different deposits on the SCC susceptibility of single-crystal nickel-based superalloys at different temperatures is crucial. This study investigated the effect of NaCl, sea salt and 80/20 mol% Na2SO4/K2SO4 on the SCC susceptibility of CMSX-10 at 550 °C and 700 °C. The results suggest that chlorine-containing salts play an important role in accelerating stress corrosion cracking at 550 °C, where the formation of HCl leads to the breaking down of the oxide and exposing the base alloy to a sulphidation environment. At 700 °C stress corrosion cracking is accelerated by the mix of sulphates that lead to reduced melting points, where the 80/20 mol% Na2SO4/K2SO4 has shown the highest susceptibility to SCC.
Correction detailed at: https://doi.org/10.1007/s11085-026-10419-w In this article the wrong figure appeared as Fig. 4 (b) specifically in the number of cracks in the sea salt salted sample at 500 h. The number of cracks that shows up on the plot at 500 h is 48, but it should be 102. In addition to the above, in page 16, the sentence in the last paragraph stating “Sea salt showed a very similar behaviour to NaCl in terms of the number of stress corrosion cracks initiated” should have been “Sea salt showed a significantly higher number of cracks than NaCl only after 200 h and 500 h of exposure.”
Keywords: 4302 Heritage, Archive and Museum Studies; 40 Engineering; 43 History, Heritage and Archaeology; C-ring; Hot corrosion; Stress corrosion cracking; Superalloys